Financial Statement Analysis in the Technology Sub-Sector Companies Listed on the Indonesian Stock Exchange - Halleina Rejeki Putri Hartono; Ulfa Rahmawati; Permatasari Cahyaningdyah; Nova Maulud Widodo; Diah Sulis Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the performance of financial reports based on financial ratio analysis for technology sub-sector companies listed on the Indonesia Stock Exchange. The financial reports used are for the last five years. The method used is descriptive analysis. The financial ratios used are the liquidity ratio, solvency ratio, profitability ratio, and activity ratio. The results of this research show that there are companies in this industry that have had thin profitability for several years. Another thing shows that companies in this industry depend on debt, but there has been an improvement in company liquidity as well.